Inhibitory Potential of Antifungal Drugs on ATP-Binding Cassette Transporters P-Glycoprotein, MRP1 to MRP5, BCRP, and BSEP - Lempers, Vincent J. C.; van den Heuvel, Jeroen J. M. W.; Russel, Frans G. M.; Aarnoutse, Rob E.; Burger, David M.; Brüggemann, Roger J.; Koenderink, Jan B. (Antimicrobial agents and chemotherapy, 2016)
Inhibition of ABC transporters is a common mechanism underlying drug-drug interactions (DDIs). We determined the inhibitory potential of antifungal drugs currently used for invasive fungal infections on ABC transporters P-glycoprotein (P-gp), MRP1 to MRP5, BCRP, and BSEP in vitro . Membrane vesicles isolated from transporter-overexpressing HEK 293 cells were used to investigate the inhibitory potential of antifungal drugs (250 μM) on transport of model substrates. Concentration-inhibition curves were determined if transport inhibition was >60%. Fifty percent inhibitory concentrations (IC 50 s) for P-gp and BCRP were both 2 μM for itraconazole, 5 and 12 μM for hydroxyitraconazole, 3 and 6 μM for posaconazole, and 3 and 11 μM for isavuconazole, respectively. BSEP was strongly inhibited by itraconazole and hydroxyitraconazole (3 and 17 μM, respectively). Fluconazole and voriconazole did not inhibit any transport for >60%. Micafungin uniquely inhibited all transporters, with strong inhibition of MRP4 (4 μM). Anidulafungin and caspofungin showed strong inhibition of BCRP (7 and 6 μM, respectively). Amphotericin B only weakly inhibited BCRP-mediated transport (127 μM). Despite their wide range of DDIs, azole antifungals exhibit selective inhibition on efflux transporters. Although echinocandins display low potential for clinically relevant DDIs, they demonstrate potent in vitro inhibitory activity. This suggests that inhibition of ABC transporters plays a crucial role in the inexplicable (non-cytochrome P450-mediated) DDIs with antifungal drugs.